The Effectiveness of Prenatal Yoga on Ballard Score and Newborn Babies Anthropometry - Longulo, Olkamien Jesdika; Pont, Anna Veronica; Mangun, Mardiani; Rafika, R (Universitas Aisyah Pringsewu, 2021)
A preliminary study at the Sriwaty Midwifery Independent Practice Clinic, the number of pregnant women in 2019 was 350-400 deliveries and 45 Premature / LBW. Prenatal yoga have never been implemented in prenatal classes.Aim and Objectives To analyze the effectiveness of prenatal yoga in pregnant women in the I-III trimester on Ballard score and anthropometry of newborns.This study is a pre-experimental study with a randomized controlled trial two group design. The sample size in the study was 40 respondents: the intervention group was 20 respondents and the control group was 20. The sampling technique was based on the consecutive sample. The statistical test is the independent t-test to determine the difference in mean Ballard score, anthropometry of newborn babies in each group. Because the sample used was 50 respondents, the normality test used was Shapiro-Wilk and the comparative hypothesis test for the numeric variable distribution was not normal is the Mann-Whitney non-parametric test.The prenatal yoga program is effective for Ballard Score, Body Length, Body Weight and Head Circumference of Newborns . It is hoped that it can become a program and be implemented in the prenatal class.Abstrak: Studi pendahuluan di Klinik Praktik Mandiri Bidan (PMB) Sriwaty, jumlah ibu hamil yang melahirkantahun 2019 sebanyak 350-400 dan 45 Prematur/BBLR. Prenatal yoga belum pernah dilakukandi kelas prenatal.TujuanMenganalisis efektivitas prenatal yoga pada ibu hamil trimester I-III terhadap skor Ballard dan antropometri bayi baru lahir.Penelitian ini merupakan penelitian pra-eksperimen dengan rancangan randomized controlled trialdua kelompok. Besar sampel dalam penelitian ini adalah 40 responden: kelompok intervensi 20 responden dan kelompok kontrol 20 responden. Teknik pengambilan sampel berdasarkan consecutive sample. Uji statistik adalah independent t-test untuk mengetahui perbedaan rerata skor Ballard, antropometri bayi baru lahir pada masing-masing kelompok. Sampel yang digunakan 50 responden sehinggauji normalitas yang digunakan adalah Shapiro-Wilk dan uji hipotesis komparatif untuk distribusi variabel numerik tidak normal adalah uji non parametrik Mann-Whitney. Program prenatal yoga efektif untuk Skor Ballard, Panjang Badan, Berat Badan dan Lingkar Kepala Bayi Baru Lahir. Diharapkan dapat menjadi program dan diimplementasikan di kelas prenatal.